Primary Biliary Cirrhosis: Environmental Risk Factors - Dronamraju, Deepti (IOS Press, 2010)
Primary biliary cirrhosis (PBC) is an autoimmune disease of unclear etiology. It is a chronic, progressive condition that causes intrahepatic ductal destruction ultimately leading to symptoms of cholestasis, cirrhosis and liver failure. The disease predominantly affects middle aged Caucasian women. It has a predilection to certain regions and is found in higher incidences in North America and Northern Europe. It also has a genetic predisposition with a concordance rate of 60% among monozygotic twins. Combinations of genetic and environmental factors are proposed in the pathogenesis of this disease with a compelling body of evidence that suggests a role for both these factors. This review will elucidate data on the proposed environmental agents involved the disease's pathogenesis including xenobiotic and microbial exposure and present some of the supporting epidemiologic data.